2015
DOI: 10.1016/j.irfa.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Are gold and silver a hedge against inflation? A two century perspective

Abstract: This study examines the long-run hedging ability of gold and silver prices against alternative measures of consumer price index for the UK and the US. We employ a dataset that spans from 1791 to 2010, and both a time-invariant and a time-varying cointegration framework. We find that gold can at least fully hedge headline, expected and core CPI in the long-run. This ability tends to be stronger when we allow for the long term dynamics to vary over time. The inflation hedging ability of gold is on average higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(91 citation statements)
references
References 45 publications
7
82
1
1
Order By: Relevance
“…The Bierens and Martins (2010) test approximates the cointegrating vector in the Johansen (1991) test by a finite number of Chebyshev time polynomials and can be used to determine whether or not the cointegrating vector varies with time. We follow Bampinas and Panagiotidis (2015) in reporting results for m up to four and conclude that time-variation is observed unless at least one m fails to rejects the null hypothesis. Note: In contrary to popular tests for cointegration, the Gregory and Hansen (1996) test allows the cointegrating vector to change at a single unknown time during the period considered.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The Bierens and Martins (2010) test approximates the cointegrating vector in the Johansen (1991) test by a finite number of Chebyshev time polynomials and can be used to determine whether or not the cointegrating vector varies with time. We follow Bampinas and Panagiotidis (2015) in reporting results for m up to four and conclude that time-variation is observed unless at least one m fails to rejects the null hypothesis. Note: In contrary to popular tests for cointegration, the Gregory and Hansen (1996) test allows the cointegrating vector to change at a single unknown time during the period considered.…”
Section: Resultsmentioning
confidence: 89%
“…Influenced by Beckmann and Czudaj (2013), we take into account CPI rates, PPI rates and money supply. We further take the formal approach of the two earlier mentioned time-variation papers (Batten et al (2014) and Bampinas and Panagiotidis (2015)), introducing a formal test for time variation in inflation and find evidence for such variation in our data set. Table 1 displays the findings of previous papers focused on the relationship between gold and inflation, as well as the inflation rate used.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings reconfirmed by Shahbaz et al (2014) for Pakistan and Batten, Ciner, and Lucey (2014) for United States. Recently, Bampinas and Panagiotidis (2015) examined the hedging ability of metal commodities for United States and United Kingdom using a large data set and found that gold maintains its status against increase in the general price level than silver in both economies. For hedging potentials of oil, a few authors found that hedge ratios are time varying.…”
Section: Review Of Literaturementioning
confidence: 99%